2018
DOI: 10.22456/1679-9216.85945
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia in a Dog Chronically Infected with Leishmania spp. and Other Infectious Agents

Abstract: Background: Rare studies have described the association of hematopoietic tumors and canine visceral leishmaniosis, however the association between the parasitary disease and neoplasia is still not well established in dogs. Thus, the aim of the present study was to report a case of acute myeloid leukemia (AML) in a dog infected by Leishmania spp. and otherinfectious agents.Case: A 8-year-old, male Poodle, was brought to the Veterinary Hospital from Universidade Federal Rural do Semi-Árido. The dog had a history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Previous cases in veterinary medicine have mainly reported an association between Leishmania and canine transmissible venereal tumor [27][28][29][30][31]. Other sporadic cases have reported the simultaneous presence of Leishmania and fibrosarcoma [14], perianal or adrenocortical adenoma [14,32], blood malignancies such as multiple myeloma [33] and acute myeloid leukemia [34], or different types of lymphomas located in various body sites [2,[14][15][16]. To the best of our knowledge, this is the first reported case of leishmaniasis as an unexpected diagnosis during the evaluation of pancytopenia in a dog undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous cases in veterinary medicine have mainly reported an association between Leishmania and canine transmissible venereal tumor [27][28][29][30][31]. Other sporadic cases have reported the simultaneous presence of Leishmania and fibrosarcoma [14], perianal or adrenocortical adenoma [14,32], blood malignancies such as multiple myeloma [33] and acute myeloid leukemia [34], or different types of lymphomas located in various body sites [2,[14][15][16]. To the best of our knowledge, this is the first reported case of leishmaniasis as an unexpected diagnosis during the evaluation of pancytopenia in a dog undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that L. infantum triggers a series of bone marrow abnormalities in infected dogs, including dysplastic changes and erythrophagocytosis [15]. It has thus been suggested that the prolonged antigenic stimulation and chronic immunosuppression that typically occurs in dogs chronically infected with Leishmania can play a crucial role in the etiopathogenesis of some hematopoietic malignancies, such as T-cell lymphoma [15] and acute myeloid leukemia [34]. However, all dogs in previously reported cases were found to be chronically infected with Leishmania at the same time as the diagnosis of the tumor [2,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%